Clinical Profile of Patients Presenting with Low Back Pain to Out Patient Department of a Tertiary Level Hospital - Thapa, Pradeep; Lakhey, Rajesh B; Shrestha, Binay L (Journal of Institute of Medicine Nepal, 2020)
Introduction Low back pain is experienced by most of the people at some point of life. In our setting, there are very limited data on low back pain. This study aims to elaborate demographic and clinical profile of patients presenting to outpatient department of Orthopedics, in Tribhuvan University Teaching Hospital with complaints of low back pain. Methods A descriptive cross-sectional observational study was carried out in 150 patients who presented with complaints of lower back pain in outpatient department of Orthopedics of TU Teaching Hospital from May to November 2019. The demographics including age, gender, occupation, and clinical data- duration of symptoms, body mass index, VAS score and radiculopathy along with Body Mass Index of each patient were recorded in a proforma separately. Results Out of total 150 patients, male: female ratio was 1:1.9. The average age of patients was 42.1 years The average height, weight and body mass index of patients were 157 cm, 61.81kg and 24.83kg/m2 respectively. The mean visual analogue score of patients was 5.41. Occupationally, predominant number of patients were housewives (41.3%). Seventy nine patients (52.7%) had low back pain alone. Seventy one patients (47.3%) had low back pain associated with radicular symptoms, out of which 74.6% had unilateral radiculopathy. Conclusion Low back pain is most commonly seen in fourth decade of life. More females as compared to males are affected with low back pain. The radiculopathy associated with low backache is mostly unilateral.